Hexapleomera urashima sp. nov. (Crustacea: Tanaidacea), a tanaidid epibiotic on loggerhead sea turtles at Yakushima Island, Japan - Tanabe, Yuki; Hayashi, Ryota; Tomioka, Shinri; Kakui, Keiichi (Zootaxa, 2017)
We describe Hexapleomera urashima sp. nov. from the carapaces of loggerhead sea turtles (Caretta caretta) on Yakushi-ma Island, southwestern Japan, the primary nesting site for the North Pacific population of this turtle. Hexapleomera urashima closely resembles H. edgari Bamber collected from Australian loggerheads (South Pacific population), sharing a uropod with four articles and maxillipedal endites with distal spiniform setae, but differs in having the maxillipedal coxa with two simple setae, the maxillipedal endite with two tiny dorsosubdistal and two distal spiniform setae, the labial palp fused to the outer lobe of the labium, and the basal article of pleopod 3 without inner setae. Several characters (e.g., size or presence/absence of a dorsal triangular process on the male fixed finger; number of inner setae on the pleopodal endopod), assumed to be diagnostic for species in Hexapleomera, actually vary within H. urashima, indicating that reassessment of species diagnoses is warranted. Hexapleomera urashima showed two COI haplotypes differing by one substitution, but separated from representatives of four other genera by 32.2–48.4% K2P distance. Indices of saturation substitution indicated that COI is not useful for phylogeny reconstruction within Tanaididae.